Analysis Of Aftershock Decay West Pasaman Earthquake 25 February 2022 Using Geostat Software Version 2.0 for Seismic Risk Reduction - Takhul Bakhtiar (Journal of Geology Sriwijaya, 2023)
There has been an earthquake in the West Pasaman Region with a magnitude of M6.1 on February 25, 2022 at coordinates 0.15° North Latitude and 99.98° East Longitude with a depth of 10 km. This event resulted in a series of aftershocks. This study aims to analyze the decay time of aftershocks that occurred in the area as a mitigation measure and reduce the risk of earthquakes. The method used in this research is the method of Mogi I, Mogi II, Omori and Utsu in GEOSTAT V2.0 software. This study uses the earthquake repository data BMKG for a period of 7 days since the Mainshock occurred. The calculation results show that aftershocks are predicted to decay on the 36th day for the Mogi I method (r = -0.88135), the 11th day for Mogi II (r = -0.93627), the 36th day for Utsu ( r = -0.88184) and day 39 for Omori (r = 0.95683). A suitable method for predicting the decay time of aftershocks is the Omori method (r = 0.95683). Estimated time of aftershock decay can be used as an effort to mitigate and reduce the risk of earthquakes.